Evaluation of Peridynamics and Its Application in Harmonic-Structured Material Simulations - de Sousa,Theodor (2020)
Materials are constantly sought to be improved in different manners. Two of the most common characteristics to improve are strength, and ductility. Historically, materials are modified homogeneously to achieve improvement, while the past century has also seen composite materials becoming standard-issue within various industries. Just recently the concept of heterogeneously modifying material micro-structures has gained prominence. One such concept is the harmonic-structured material. It consists of the same material, but topologically controlled to yield two different modes organised in a repeated manner, possessing high strength and high ductility respectively. Harmonic structured materials exhibit favourable characteristics, but the precise behaviour of the deformation of the material is yet to be understood in-depth. Computational modelling is a great asset in this behaviour evaluation, but as the length-scales of the modes and the topology are relatively large, modelling using molecular dynamics is not suitable. Neither are regular classical continuum mechanics simulations, which are incapable of modelling fracture in materials. Both of these issues are addressed by a certain formulation of continuum mechanics called peridynamics. This master thesis, written at the division of mechanics at the faculty of engineering at Lund University, has applied the peridynamic theory to harmonic-structured nickel using the Peridigm software in order to evaluate the utility of peridynamics in the field of harmonic-structured materials, mainly focusing on fracture behaviour. In the thesis, the modal component materials are subjected to uniaxial tension in order to calibrate a linear elastic-plastic material model of experimental data. A proof-of-concept simulations of harmonic-structured nickel are also performed. The calibration simulations fail to properly model the experimental data regarding stress localisation and fracture. The cause for absence of fracture is attributed to the use of a numerical solver which disregards velocities, and the cause for the lack of stress localisation is believed to originate partly from the linear behaviour of the strain-hardening modulus. The proof-of-concept simulation of harmonic-structured nickel is capable of modelling both wave initiation, propagation, and reflection, as well as fracture initiation and propagation. Peridigm, as a tool for material modelling, is found to be subpar regarding efficiency when compared to commercial classical continuum mechanics software. This is mainly due to its development status, lack of documentation, support, and implemented utilities. However, Peridigm is an open-source initiative and therefore could be customised extensively. Overall, it is most certainly a useful tool for research on peridynamics.
Keywords: peridynamics; peridigm; harmonic-structured materials; computational mechanics; fracture modelling